PERSEPSI MASYARAKAT TERHADAP KONVERSI LAHAN MENJADI PERKEBUNAN KELAPA SAWIT DI DESA NANGA TAYAP KECAMATAN NANGA TAYAP KABUPATEN KETAPANG - Yeyen, .; Muin, Sudirman; Fahrizal, . (Universitas Tanjungpura, 2018)
The land conversion into oil palm plantations creates perception in the community. The aim of this research is to examine community perceptions on the conversion of land to oil palm plantations in Nanga Tayap Village, Nanga Tayap Sub-District, Ketapang District, and to examine the correlation between factors that influence communities on the conversion of land into oil palm plantations. Factors that influence the perceptions are: (1) level of knowledge (2) income and (3) land area. The researcher applied a descriptive analysis and inferential analysis using Pearson’s correlation test, in which each was given the score and observation result in Likert scale. The results of this research indicate peoples’ perceptions on the conversion is positive with frequency value of 34 (47.89%), the correlation between the level of knowledge and land area is significantly positive, it gives a significant value to the community perceptions towards the conversion of land into oil palm plantations. Whereas, community perceptions and income level correlation is positive but insignificant. It shows that as community get their high income from the conversion, their perceptions towards the conversion of land into oil palm plantations would be affirmative.Keywords: Community, Land Conversion, Oil Palm Plantation and Perception